Instagram dan Kesehatan Mental Generasi Z di Yogyakarta - Azaria, Ayatusy Syifa; Ratnasari, Desy; Sumawati, Annisa Ramadhina (Jurnal Mahasiswa Komunikasi Cantrik, 2024)
Nowadays, Instagram is a social media platform widely used by Generation Z or Gen Z. Excessive or continuous use of Instagram daily can impact the mental health of its users. This research aims to analyze the use of Instagram on the mental health of Generation Z in the Yogyakarta region. The research employs a qualitative method with a case strategy. Data collection was conducted through in-depth interviews with informants. The study subjects were  three individuals who met the criteria: being part of Generation Z (born between 1997-2012), having an Instagram accounts, and residing in Yogyakarta. The results found that Instagram use plays a role in the mental health of Generation Z. The interviewed informants generally reduced their Instagram usage because they felt it negatively impacted their sense of security and caused anxiety. This study recommends the importance of larger-scale research that could be connected to family and social enviroments.